The association between proton pump inhibitors and myocardial infarction: What do food and drug administration data tell us? - Jiun Ming Tan; Richard Parsons; Tin Fei Sim; Ya Ping Lee (Wolters Kluwer Medknow Publications, 2019)
Objective: There is limited and conflicting evidence on the association between proton pump inhibitors (PPIs) and myocardial infarction (MI). This study aims to examine the occurrence of MI associated with PPI use from the Food and Drug Administration (FDA) Adverse Event Reporting System database. Methods: This is a cross-sectional study using data from the FDA dated from December 2013 to April 2018. Standard descriptive statistics were used to describe demographic information. Logistic regression analyses were performed to investigate the association between the independent variables and MI. Findings: Among the 52,443 individuals who were taking a PPI and experienced an adverse event which was registered on the FDA database, 726 (1.38%) experienced MI. Of all the PPIs, esomeprazole had the largest proportion of users experiencing MI (1.81%). Compared to other PPIs, esomeprazole was associated with a significantly higher rate of MI (odds ratio [OR] =1.53, P < 0.001), whereas lansoprazole was associated with a lower rate of MI (OR = 0.74, P = 0.03). Conclusion: Among the PPIs, esomeprazole appeared to have the highest risk of MI. Although the observed associations do not infer causality, this study highlighted a need for further studies to determine if a PPI, especially esomeprazole, can indeed cause MI.